Digital Parenting to Children Using The Internet - Muhamad Yusuf; Doli Witro; Rahmi Diana; Tomi Apra Santosa; Annisa ‘Alwiyah Alfikri; Jalwis Jalwis (Pedagogik Journal of Islamic Elementary School, 2020)
Based on survey data released by the Association of Indonesian Internet Service Providers (APJII), it is stated that, in 2018, out of 171.17 million people who have used the internet, 60.8% of them are children aged 5 to 19 years. The irony of the use of the internet has reached children who incidentally are still shallow on the issue of the negative impact and the positive impact of the internet. Departing from the harmful effects and positive effects caused by the internet, the author wants to do a study of digital parenting for children. This research is a qualitative study and is library research. The required data comes from books, journals, and articles. After the data is collected, it is then analyzed and analyzed inductively and deductively and is linked and compared (comparative). This study aims to prevent children from accessing harmful content so that children tend to access only positive content. The analysis result shows that good parenting in the digital era is an authoritative parenting style (contextual) and authoritative parenting style (democratic), where this parenting style is a parenting style suitable for children in the digital age.